Bicycle and pedestrian harmony: perspectives on bicyclists behavior on campus - Scott, John J. (Kansas State University, 2014)
In the past 20 years, the promotion of bicycle-friendly environments in the United States has become a major topic for city planners, engineers, landscape architects, and concerned citizens. The City of Manhattan, Kansas, and Kansas State University (KSU) are following the trend by creating more bicycle infrastructure. As an example, the Campus Planning and Facilities Management Department at KSU recently installed new signs on the pavement that support existing bicycle rules around campus. The rules require cyclists to dismount and walk their bicycles on the main campus sidewalk and yield to pedestrians when crossing Bosco Plaza. While signs are important, these markers should be part of a bigger plan that includes infrastructure, education and enforcement working together to create a safe, active transportation system. This project explores bicycling culture at KSU campus and uses three key concepts of infrastructure, education, and enforcement to discover what improvements are needed and what improvements can be made. The video-based observation method consists of recording the activity of cyclists entering the campus core and analyzing the behavior of cyclists and pedestrians. The survey was conducted via social media in order to understand safety perceptions and behaviors of bicyclists and pedestrian as daily commuters to campus. The results from both methods show a lack of involvement with infrastructure, education, and enforcement for cycling at Kansas State which creates areas that are not safe for pedestrians. Bicycling (15.4%) and walking (46.7%) represent 62.1% of commuters to campus; therefore, a safer approach to campus infrastructure needs to be addressed for these users. Results indicate that the dismount signs are ignored 82.9% of the time, and collisions between cyclists and pedestrians do happen on campus. An absence of enforcement is shown in the data, which is compounded by a non-existing bicycling education program, making for a less than optimal active transportation system on campus.
Keywords: Bicycle; Pedestrian; Safety; Active transportation; Urban Planning (0999)